SANKSI PIDANA TAMBAHAN BAGI PELAKU KEKERASAN SEKSUAL ANAK - Hb Sujiantoro (Faculty of Law, Universitas Pattimura, 2017)
Violence especially sexual violence in children lately occurred in the midst of society. The media, both print and electronic almost daily, present news related to sexual violence, in which children are victims of perpetrators. On that occasion, there was a strong public reaction by condemning the actions of the perpetrators, they requested that the perpetrators be punished with the most severe punishment and some even ask the perpetrators to be punished by the law and sentenced to death. Given the cruel acts of the perpetrators not only arise the reaction of the community, but make the government, from the President, Social Minister, Minister of Justice and Human Rights and others, also members of the House voted to condemn the barbaric acts of the perpetrators and requested that perpetrators be punished weighing.In response to this, the Government in this case President Joko Widodo on May 25, 2016 signed the Government Regulation in Lieu of Law (PERPPU) No. 1 of 2016 on the Second Amendment to Law No. 23 of 2002 on Child Protection. Which according to the term is generally called PERPPU Kebiri. The PERPPUalso regulates sanctions for heavier offenders also regulating additional criminal sanctions. Furthermore, on May 9, 2016 this PERPPU is set to become Law No. 17 of 2016. Given the importance and the need for security and free from threats to children, the protection of the victims is necessary so that he has a better future. Because it is related to the future of the nation, it is appropriate that additional punishment (the other and the other) for the perpetrator of child sexual violence. For the sake of justice, additional criminal sanctions of chemical curiosity, installation of electronic detection devices (chip), and announcement of the identity of perpetrators to the public for child sex offenders are considered effective, because it can: 1). Cause the deterrent effect for the perpetrator 2) .Press the action of sexual crime (especially in the short term), because the potential perpetrators are afraid and think again if they want to repeat the action again 3). Providing protection against victims (children) from sexual violence.